Radioactivity in staple foodstuffs and concomitant dose to the population of Jigawa state, Nigeria - Hassan, Y. M.; Zaid, H. M.; Guan, B. H.; Khandaker, Mayeen Uddin *; Bradley, D.A. *; Sulieman, A.; Latif, S. A. (Elsevier, 2021)
In addition to the presence of primordial radionuclides, inputs from technological progress together with nuclear technology proliferation have also contributed to the level of radioactivity in the soil. Due to the transfer of radionuclides in the chain soil-plant-human, notably via the ingestion pathway, it is important to assess the concentrations of radioactive materials in staple foodstuffs. Present study via HPGe γ-ray spectrometry was undertaken to measure the concentrations of 226Ra, 228Ra and 40K in the more prominent staple Nigerian foodstuffs (rice, wheat, and millet). For 226Ra, 228Ra and 40K, the activity concentrations (Bq/kg) in rice were in the respective range of 0.9–2.4, 0.5–2.4 and 78–326, while for wheat they were 1.3–5.1, 0.7–1.2 and 192–264, and for millet the range of 2.5–9.9, 0.8–1.9 and 186–197 in the same order. Overall, the measured data were found to be below the global average values of 67 Bq/kg, 82 Bq/kg and 310 Bq/kg prescribed by UNSCEAR for 226Ra 228Ra and 40K, respectively. The committed effective dose via consumption of the studied foodstuffs shows millet to have the greatest contribution, albeit not superseding the dose limit of 290 μSv/y proposed by UNSCEAR. The threshold consumption rates for the studied foodstuffs were within the range of 66–343 kg/y (mean value 153 kg/y), approximating to individual consumption of ~ 419 g/d, not equating to unacceptable radiological risk. The lifetime cancer risk from consumption of the studied food was also assessed and found to be below the ICRP (2013) cancer risk factor of 4.5 × 10-3 based on an additional annual dose limit of 1 mSv (above background) for the general public. In summary, consumption of the studied foodstuffs poses an insubstantial threat to the public.